Community-Based Economic Capacity Development for Sustainable Coastal Development in Serang City - Mirajiani, Mirajiani; Hamzah, Asep; Widiati, Siti (Agrikan Jurnal Agribisnis Perikanan, 2022)
Marine and fishery development is closely related to coastal development since the majority of the development actors in the fishery and marine sectors are coastal communities. Economic capacity development of an area is an attempt to realize sustainable coastal development. This study aims to elaborate to what extend the community economic capacity development and how the development policies of the government are in supporting the community economic capacity development. The study uses qualitative and quantitative methods (a mixed method). The qualitative method employs data collection techniques in the form of observations, in-depth interviews, and focus group discussion (FGD). The quantitative method applies data collection techniques of structured interviews and a survey technique. Supported by local development policies that have been formulated in the mid-term and long-term development plans, the community-based economic capacity development in the coastal areas of Serang City aims at improving the economic prosperity of the coastal community as well as improving coastal area management. At large, the economic capacity development consists of (1) improvement of human resource capacity, (2) enhancement of economic competitiveness and (3) improvement of economic facilities/infrastructures as the support. The conomic capacity improvement involves full participation of communities and stakeholders who mutually interact, collaborate, and cooperate to enhance each capacity and together they encourage coastal economic improvement.